Fast camera imaging of plasmas in Alcator C-Mod and W7-X. (December 2018) - Ballinger, S.B.; Terry, J.L.; Baek, S.G.; Tang, K.; von Stechow, A.; Killer, C.; Nicolai, D.; Satheeswaran, G.; Drews, P.; Grulke, O.; ,
Highlights: Edge turbulent filaments travel up the inner divertor leg in Alcator C-Mod. Large rotating filaments are observed during plasma radiative collapse in W7-X. Visible light from the divertor in W7-X fluctuates at around 1.4 kHz in the standard magnetic configuration. Edge gas fueling efficiency in W7-X appears to be lower at higher densities, based on rough estimates of line radiation proportions. Abstract: In this work we present an analysis of fast-camera imaging of Alcator C-Mod's divertor region and of the plasma cross section in the W7-X stellarator. In C-Mod, the dynamics of intermittent edge plasma filaments are imaged at 397, 100 frames per second in an oblique view. An automatic pipeline was developed to reconstruct the filament motion in the R, Z plane of the divertor using EFIT field line projections. Next, we added our fast-framing camera to W7-X's diagnostic suite for the 2017 run campaign, the first with a divertor. It has a tangential view of the machine cross section, including part of a divertor module. The view is coupled to the camera via a coherent fiber bundle. The spatial resolution is 2–4 cm and the typical plasma brightness limits the fastest usable frame rate to 30k frames/s. We observe filaments in the plasma boundary that rotate around the magnetic axis during radiative collapse; filaments were observed in steady state in the limiter configuration of W7-X by Kocsis et al.[1] . We also observe for the first time a 1–2 kHz quasi-coherent fluctuation in divertor target emissions in the W7-X "standard" magnetic configuration. Finally, a rough analysis of edge gas fueling efficiency using fast camera data and S/XB coefficients finds that fueling is less efficient at densities higher than 4 × 10 19 m −3 .